Management of single-rooted maxillary central incisor with two canals: A case report - krishnamurti, anantanarayanan; velmurugan, natanasabapathy; nandini, suresh (Iranian Endodontic Journal, 2011)
The aim of this study was to report the endodontic management of right maxillary central incisor having two canals with Vertucci canal configuration type IV. Internal morphology of root canals is variable and often complex. Therefore, to achieve a technically satisfactory endodontic outcome, the clinician must have adequate knowledge of the internal canal morphology and its variations in order to debride and obturate the root canal system thoroughly.